Limericks for Myocardial Recovery and Regeneration - James B. Young; Albert E. Raizner (Methodist DeBakey Cardiovascular Journal)
Limericks are an easy, casual, and entertaining way to have fun with the English language. Creating them can be an engaging pastime to assist in memorizing important anatomic relationships necessary for being an interventional cardiologist or simply an intellectual exercise that provides respite after a hectic day in the cardiac catheterization laboratory, surgical suite, outpatient clinic, or intensive care unit. Interest in this form of poetry often dates back to when we, as children, were taught the simplistic rhyming pattern of a traditional limerick or learned one during adolescence. As we age, our limericks often became more humorous, personal, and bawdy. That evolution is the beauty of this poetic form. For this edition of Poet’s Pen, we invited Dr. Marshall S. Flam, a noted dabbler in the limerick world, to pen “Limericks for Myocardial Recovery and Regeneration” to accompany the theme of this issue.